Iron:The missing link of depression prevention and treatment - reza pakzad; Mohammadamin Jandaghian Bidgoli; fatemeh abdi; negin shaterian (Journal of Biostatistics and Epidemiology)
Objective: To identify the effect of Iron as a preventive and therapeutic agent on depression and other hematological indices by a systematic review and meta-analysis. Methods: International databases like Web of Science, PubMed, Cochrane,  International Clinical Trials Registry Platform, Clinicaltrials.gov, and Scopus were searched until 27 July 2024 to identify eligible articles with the appropriate Medical Subject Headings (MeSH).  The risk of bias tool for randomized trials (RoB 2) was used for precise assessment.  Heterogeneity was determined using Cochran’s Q-test and the I2 index. To assess source of heterogeneity, meta-regression was used. The pooled standardized mean difference (PSMD) was calculated by considering the random effects model. Results: of 2154 studies,14 studies were included in systematic review and 6 studies were excluded from analysis due to lack of data for calculating PSMD and finally, 8 studies were included in meta-analysis. Based on the results, iron therapy led to improvement in depression symptoms (PSMD = -0.18; 95% CI: -0.32 to -0.03). The iron therapy led to increasing the blood level of Iron (PSMD = 0.57; 95% CI: 0.19 to 0.95), Ferritin (PSMD = 0.55; 95% CI: 0.25 to 0.85), HCT (PSMD = 0.40; 95% CI: 0.18 to 0.61), MCV (SMD = 0.67; 95% CI: 0.18 to 1.15) and Transferrin saturation (PSMD:0.26; 95% CI: 0.02 to 0.50). Based on the meta-regression result, the sample size, participant age, and publication year had no significant role in heterogeneity between studies. Conclusion: The use of iron supplements in patients with depression can be considered. However, there is a need to conduct further studies involving various kinds of depression.